2023
DOI: 10.1212/wnl.0000000000207810
|View full text |Cite
|
Sign up to set email alerts
|

Patient Travel Distance to Neurologist Visits

Chun Chieh Lin,
Chloe E. Hill,
Kevin A. Kerber
et al.

Abstract: Background and Objectives: The density of neurologists within a given geographic region varies greatly across the US. We aimed to measure patient travel distance and travel time to neurologist visits, across neurologic conditions and subspecialties. Our secondary goal was to identify factors associated with long-distance travel for neurologic care. Methods: We performed a cross-sectional analysis using a 2018 Medicare sample of patients with at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…22 Approximately 20% of Medicare beneficiaries live 50 miles or more from their neurologist, and those living 50 miles or more were 26% less likely to follow up compared with those who lived closer than 50 miles. 22 Telehealth does improve access to care for some 23 ; however, with the expansion of these services, existing disparities may not be improved and are sometimes exacerbated, creating a worsening digital divide. Studies looking at the adoption of teleneurology during the COVID-19 pandemic showed that older men of color and those with Medicare or Medicaid were less likely to complete video visits compared with younger White women with private insurance.…”
Section: Telehealth-related Disparitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Approximately 20% of Medicare beneficiaries live 50 miles or more from their neurologist, and those living 50 miles or more were 26% less likely to follow up compared with those who lived closer than 50 miles. 22 Telehealth does improve access to care for some 23 ; however, with the expansion of these services, existing disparities may not be improved and are sometimes exacerbated, creating a worsening digital divide. Studies looking at the adoption of teleneurology during the COVID-19 pandemic showed that older men of color and those with Medicare or Medicaid were less likely to complete video visits compared with younger White women with private insurance.…”
Section: Telehealth-related Disparitiesmentioning
confidence: 99%
“…One of the advantages of telehealth is thought to be improved access by reducing the need for patients to travel. Although 20% of the US population resides in rural areas, only 9% of physicians and 10% of specialists practice in these areas 22 . Approximately 20% of Medicare beneficiaries live 50 miles or more from their neurologist, and those living 50 miles or more were 26% less likely to follow up compared with those who lived closer than 50 miles 22 .…”
Section: Telehealth-related Disparitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with the advent of new genetic diagnostic tools, most patients have limited access to neurological care [132,133] and/or medical genetics services [2,134,135], and concentrated expertise in rare diseases limits the scope of expedient and accurate diagnosis of adult patients with neurogenetic diseases. Collaboration between neurologists and geneticists is needed to better incorporate clinical and genetic data.…”
Section: Barriers To Neurogenetic Testingmentioning
confidence: 99%
“…Our finding that Black patients travel shorter distances does not mean that Black patients have better access to neurologic care compared with White patients. 1 Transportation insecurity is one potential reason that travel distance might have been shorter for Black patients. Furthermore, we focused on travel distance, but other measures of access such as seeing an outpatient neurologist and referrals to subspecialists care were not studied and are also important.…”
mentioning
confidence: 99%